Caracterización de Candida spp., en aves psitácidas para conocer su prevalencia y sensibilidad antifúngica en el Eco-zoológico San Martín - Reinoso Chávez, Gladys Carolina (2024)
Avian candidiasis is mainly caused by Candida species such as C. glabrata, C. tropicalis, and C. albicans, where psittacine birds such as parrots and cockatoos are usually very susceptible, especially due to a deficiency in their immune system. Furthermore, reports of resistance to antifungal agents by this microorganism represent a zoonotic danger and for the health of birds. The present study was carried out at the San Martín Eco- Zoo located in the Baños canton, through cultures and mycological isolations carried out in the Research laboratories of the State University of Bolívar, the prevalence of Candida spp. was established, the species of this yeast and the antifungal susceptibility profile of the species found was determined. Once the results were obtained, they were analyzed and represented using tables and graphs. A 100% prevalence of Candida spp. was established, in addition, 70% of the isolates belonged to C. auris, this same yeast being the only one that occurred in all the animals and since there were no cut-off points for the susceptibility test, performed a dependent t-Student test with a result of 4.04 (p-value=0.001) being highly significant. The variables, age, body condition and weight with the presence of this fungal pathogen could not be established as predisposing factors. And when evaluating the susceptibility of the fluconazole and nystatin drugs, it was observed that the vast majority of the isolates were resistant to the antibiotics under study.